2017
DOI: 10.1039/c6md00697c
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic effects of a polysaccharide from Lachnum YM240 and its derivatives in mice, induced by a high fat diet and low dose STZ

Abstract: Carboxymethylated and sulfated polysaccharides (CLEP and SLEP) were prepared from an exopolysaccharide previously obtained from YM240 (LEP) by chemical modifications. Two doses (50 mg kg and 200 mg kg b. w.) of LEP, CLEP and SLEP were orally administered to normal mice and type 2 diabetic mice (T2DM) that were induced by streptozotocin (STZ) and a high fat diet, respectively. The hypoglycemic effect was evaluated by testing the oral glucose tolerance, fasting blood glucose (FBG) levels, fasting serum insulin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…To continue, we also reported a drop in liver GCK expression, which correlates well with one previous investigation [49]. By comparison, other reports have observed the upregulation of hepatic GCK following the intake of a polysaccharide extract [64] and a fermented product [57] in diabetic and HFD-fed mice, respectively. Our finding suggests a reduced glycolysis or glucose utilization in the liver, which would lead to greater circulating glucose levels, as well as a compromised insulin secretion [58].…”
Section: Discussionsupporting
confidence: 91%
“…To continue, we also reported a drop in liver GCK expression, which correlates well with one previous investigation [49]. By comparison, other reports have observed the upregulation of hepatic GCK following the intake of a polysaccharide extract [64] and a fermented product [57] in diabetic and HFD-fed mice, respectively. Our finding suggests a reduced glycolysis or glucose utilization in the liver, which would lead to greater circulating glucose levels, as well as a compromised insulin secretion [58].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, such a process is safe for food and pharmaceutical manufacturing. The doses of LJPC used in this study were comparable to those of polysaccharide extracts used in rodent model studies (Zha et al, 2012;Wang et al, 2017). However, it remains unclear how a maximum safe dose evaluated using experimental animals can be converted the human dose, although some studies proposed the conversion could be achieved by multiplying a conversion factor, for example a factor of 0.162 (considering the ratio of animal body weight to human body weight) (FDA, 2005) or 0.018 (considering both the ratios of body weight and body surface area between animal to human) (Reagan-Shaw et al, 2008).…”
Section: Hypolipidaemic and Antioxidant Activities Evaluated In A Moumentioning
confidence: 70%
“…Thus, LJPC could possess dosedependent hypolipidaemic capacity, and the modes of action underlying might include the inhibition of HDL oxidation at a high dose and suppression of the uptake of oxidised LDL at a medium dose (Aviram et al, 1998;Fuhrman et al, 2002). The doses of LJPC used in this study were comparable to those of polysaccharide extracts used in rodent model studies (Zha et al, 2012;Wang et al, 2017). A long-term high-fat diet likely induces several lipid metabolism disorders (Tian & Yu, 2015).…”
Section: Hypolipidaemic and Antioxidant Activities Evaluated In A Moumentioning
confidence: 84%
“…It might be one of the reasons leading to intestinal absorption reduction attributive in the hypoglycaemic effect. Furthermore, important ingredients of the extract, saponins [ 27 ] and mucilage [ 28 ], have been reported to have a strong hypoglycemic effect in the diabetic rats. Also, Rajkumar et al [ 29 ] have suggested that the extract reduced weight gain in the diabetic rats which might be due to an elevated rate of catabolism leading to muscle loss.…”
Section: Discussionmentioning
confidence: 99%